2008
DOI: 10.3168/jds.2007-0278
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Utilization in Malagueña Dairy Goats Differing in Genotypes for the Content of αS1-Casein in Milk

Abstract: A study was carried out with 20 goats of the Malagueña breed, half with a high (HG) and half with a low (LG) genetic capability for alpha(S1)-casein (AS1-CN) synthesis, to determine whether the 2 different genotypes (that cause differences in goat milk composition) are related to differences in nutritional feed utilization. Among the 10 HG goats, 7 had BB and 3 had AB genotypes for AS1-CN, whereas there were 7 EF and 3 FF genotypes in the 10 LG goats. The goats were fed diets differing in crude protein content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…Moreover, the milk yield of aa goats fed the SFB diet was 350 g/day more than that of goats fed the other diets, whereas the differences among diets were markedly lower in aF goats. These results clearly show the existence of relationships between nutrition and α S1 -Cn polymorphism, as supported by other authors [9,10], and particularly confirm the better milking response of goats with strong alleles at CSN1S1 loci, compared with FF goats, when fed higherenergy diets balanced for energy and protein content [8][9][10].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the milk yield of aa goats fed the SFB diet was 350 g/day more than that of goats fed the other diets, whereas the differences among diets were markedly lower in aF goats. These results clearly show the existence of relationships between nutrition and α S1 -Cn polymorphism, as supported by other authors [9,10], and particularly confirm the better milking response of goats with strong alleles at CSN1S1 loci, compared with FF goats, when fed higherenergy diets balanced for energy and protein content [8][9][10].…”
Section: Resultssupporting
confidence: 88%
“…Because feed also exerts a great influence on the yield and properties of goat milk, there is interest in how nutrition might interact with the genetic polymorphism at α S1 -Cn. Recent researches showed how aa goats, compared with FF goats, more efficiently utilize dietary protein [7][8][9] and respond to high-energy diets by utilizing nutrients more efficiently and achieving a higher milk yield [10].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have been carried out on the effect of diet on milk production and composition in goats at different α s1 -casein genotypes. In general, it has been shown that strong alleles are associated with a greater efficiency of N utilization, compared with weak alleles (Schmidely et al 2002; De la Torre et al 2008, 2009).…”
mentioning
confidence: 99%
“…In a previous study, De la Torre et al (2008) used goats belonging to genotypes of high and low capacity for milk α s1 -casein synthesis, and sought to determine whether the production and composition of the milk, according to the genotype, was related to differences in the nutritional utilization of the diet. At the same time, since the opinion of the authors is that it is also necessary to clarify whether the protein requirements of the animals depend on the corresponding genotype, the study took into consideration two levels of protein.…”
mentioning
confidence: 99%
“…In this respect, although some information is available on the production of goat milk depending on the genotype associated with the synthesis of α s1 -casein in milk and on the level of protein in the diet (Schmidely et al 2002; De la Torre et al 2008), the possible interaction between the factors remains unknown. The aim of the present study was to examine this question.…”
mentioning
confidence: 99%